Eaton Exponent Sensitivity in Sonic and Resistivity Log-Based Pore Pressure Prediction: Supporting Sustainable Energy Exploration in South Sembakung Field, Indonesia - Lucky Rinaldy; Abdul Haris (Jurnal Penelitian Pendidikan IPA, 2026)
Accurate pore pressure prediction is critical for safe drilling operations during early exploration when direct measurements are limited. The Eaton method is widely applied, yet the exponent (n) is treated as a fixed constant without sensitivity evaluation under normal pore pressure regimes. This study quantifies the effect of exponent variation using sonic and resistivity logs from Well X, South Sembakung Field, Tarakan Basin. Normal Compaction Trends (NCTs) were constructed from shale intervals (GR ≥ 75 API). NCT quality differs substantially between log types with R² = 0.79 for sonic versus R² = 0.076 for resistivity, causing residual deviations amplified nonlinearly by n, making exponent selection consequential even under normal pressure. Systematic variation (n = 2.50–3.50 for sonic; n = 1.00–2.00 for resistivity) was validated against three DST measurements using Mean Absolute Error (MAE). Sonic predictions yielded MAE of 309.89–402.40 psi, outperforming resistivity predictions (584.50–995.85 psi), reflecting superior NCT stability. Resistivity errors reflect petrophysical heterogeneity including formation water salinity and clay mineral content. Lower n values mechanically converge predictions toward the hydrostatic baseline as a mathematical consequence of the Eaton formulation. The Eaton exponent must therefore be treated as a site-specific calibration parameter, not a universal constant.